DOI: 10.33915/etd.3717
|View full text |Cite
|
Sign up to set email alerts
|

Coaching life skills through sport: An application of the teaching personal and social responsibility model to youth sport in eSwatini

Abstract: Coaching life skills through sport: An application of the teaching personal and social responsibility model to youth sport in eSwatini Zenzi Huysmans Adolescence is a formative developmental period where youth learn the life skills and values needed to become compassionate and civically-engaged young people and navigate increasingly challenging global environments. Youth in eSwatini face major context-specific challenges that impede their healthy development as well as limited engagement with government initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 80 publications
(354 reference statements)
0
20
0
Order By: Relevance
“…We assessed 15 studies against the QATID, a total score of 16 represented the highest score that any paper could achieve. Scores ranged from 3 to 10, with Huysmans, Clement, Whitley, Gonzalez, and Sheehy (2019) the only one to achieve a score of 10 (see Table 1).…”
Section: Quality Assessment Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed 15 studies against the QATID, a total score of 16 represented the highest score that any paper could achieve. Scores ranged from 3 to 10, with Huysmans, Clement, Whitley, Gonzalez, and Sheehy (2019) the only one to achieve a score of 10 (see Table 1).…”
Section: Quality Assessment Resultsmentioning
confidence: 99%
“…Furthermore, in line with our working definition of life skills whereby transfer is highlighted as a crucial aspect within the life skills domain, we have provided overall quality scores for the papers in which life skills development and transfer is evidenced (see Tables 2 and 4). These included the three papers identified as moderate-high quality (i.e., Bean et al, 2016;Huysmans et al, 2019;Jacobs & Wright, 2019); six of the 11 papers identified as moderate quality (i.e., Goudas & Giannoudis, 2010;Hodge Kanters, Forneris, Bocarro, & Sayre-McCord, 2017;Holt et al, 2013;Waldron, 2009;Weiss et al, 2013;Weiss, Bolter, & Kipp, 2016); and the one paper identified as low quality (i.e., Lee, Park, Jang, & Park, 2017).…”
Section: Quality Assessment Resultsmentioning
confidence: 99%
“…Internationally there are also many examples of TPSR based out-of-school or extracurricular sports-based programs. These include in Brazil where TPSR based programs in handball, dance and futsal were implemented with three different age groups (Almeida & Pick, 2018), a sport for development program with vulnerable youth in Eswatini (Huysmans, Clement, Whitley, Gonzalez, & Sheehy, 2019) and a sports-based program for adolescents in South Africa (Whitley, 2012). TPSR has also formed the basis of sport for development programs around the world including two major initiatives in Belize and Sri Lanka (Wright, Jacobs, Howell, & Ressler, 2018).…”
Section: Other Contexts and Populationsmentioning
confidence: 99%
“…In considering who delivers TPSR programs, in the majority of published studies the TPSR implementation was facilitated by a university academic delivering the program to teachers, teachers in training, or program leaders who taught TPSR within their normal program (Huysmans, et al, 2019;Severinsen, 2014). In some studies, however, the academic leader was also involved in or was fully responsible for the direct delivery to youth (Filiz, 2019;O.…”
Section: Other Contexts and Populationsmentioning
confidence: 99%
“…Good social development makes children have a good self-concept (Benninger & Savahl, 2017) and makes children easier to adjust (Santrock, 2018). The children have trust in other people (Kress & Elias, 2019), then this belief will build the children's social spirit (Huysmans et al, 2019). With this social spirit, children will create a reflection on themselves (Green, 2019).…”
Section: A Introductionmentioning
confidence: 99%